2010
DOI: 10.1111/j.1469-0691.2009.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and antimicrobial susceptibility testing of Gram-positive cocci in blood cultures by direct inoculation into the BD Phoenix system

Abstract: Rapid identification and antimicrobial susceptibility testing (AST) of the causative agent(s) of bloodstream infections are essential for the selection of appropriate antimicrobial therapy. To speed up the identification and AST of the causative agent, the fluid from blood culture bottles of a Bactec 9240 instrument (Becton Dickinson) containing Gram-positive cocci was mixed with saponin. After a 15-min incubation, the bacteria were harvested and transferred to the appropriate panel of a BD Phoenix automated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…27,28 In this study participants did not report the extent of Gram smear reporting or criteria used for identifying discrepancies. Although newer molecularbased methods can rapidly and accurately identify a wide range of different microbial species directly from positive blood cultures, [12][13][14] the impact of this technology on management and outcomes of patients with bacteremia, beyond reporting preliminary Gram smear results, is yet to be determined. 29 Previous studies have shown excellent concordance between preliminary blood culture Gram stain interpretations and final culture results.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 In this study participants did not report the extent of Gram smear reporting or criteria used for identifying discrepancies. Although newer molecularbased methods can rapidly and accurately identify a wide range of different microbial species directly from positive blood cultures, [12][13][14] the impact of this technology on management and outcomes of patients with bacteremia, beyond reporting preliminary Gram smear results, is yet to be determined. 29 Previous studies have shown excellent concordance between preliminary blood culture Gram stain interpretations and final culture results.…”
Section: Commentmentioning
confidence: 99%
“…Continuously monitoring blood culture systems detect more than half of bacteremias in 24 hours or less, and the vast majority (85%) in less than 48 hours. 20 Although certain advances in direct identification of microorganisms from blood cultures have been described, 12,13,21 the current diagnostic mainstay in routine laboratory practice is performing Gram smears from broth bottles that have signaled positive growth. The Gram stain provides a preliminary result that is vital to effectively managing patients with serious infections and has more clinical importance than does final culture results.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published direct AST protocols were validated using interpretative category breakpoints derived from Clinical and Laboratory Standards Institute (CLSI) and from DIN (Deutsches Institut für Normung), respectively [6,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, molecular methods and mass spectrometry were evaluated for rapid identifi cation from positive fl agged blood cultures with sometimes confl icting results regarding the sensitivity and the lack of AST results [4]. Among the manufacturers of blood culture systems, only Becton-Dickinson (BD) provides a protocol for direct AST from positive blood culture bottles, which is time-consuming and useful only for Gram-negative rods [5,6].…”
Section: Introductionmentioning
confidence: 99%